Cognitive Penetrability and Perceptual Justification - Siegel, Susanna (Noûs (Bloomington, Indiana), 2012)
This paper concentrates on a simple and popular theory of perceptual justification known as dogmatism. The author argues that there are cases in which dogmatism predicts that a cognitively penetrated visual experience can elevate the subject from an epistemically bad situation to an epistemically better one, yet in which it is implausible to suppose that such epistemic elevation takes place.